Preventive Hoof Trimming and Animal-Based Welfare Measures Influence the Time to First Lameness Event and Hoof Lesion Prevalence in Dairy Cows - Sadiq, Mohammed B.; Ramanoon, Siti Z.; Shaik Mossadeq, Wan Mastura M.; Mansor, Rozaihan; Syed-Hussain, Sharifah S. (Frontiers in Veterinary Science, 2021)
The objectives of this study were to, 1) investigate the impact of the Dutch five-step hoof trimming (HT) technique on time to lameness and hoof lesion prevalence in grazing (GR) and non-grazing (NGR) dairy cows, and 2) association between potential benefits of HT and animal-based welfare measures during lactation. A total of 520 non-lame cows without hoof lesions from 5 dairy farms (GR = 2, NGR = 3) were enrolled at early (within 30 days in milk; DIM) and late lactation (above 200 DIM), and randomly allocated to either trimmed (HGR or HNGR) or control groups (CON-GR and CON-NGR). Locomotion scores, body condition, hock condition, leg hygiene, and hoof lesion were assessed at monthly intervals until the following 270 days in milk. The data were analyzed using Kaplan-Meier, multivariable Cox, and logistic regression models. The overall incidence rate of lameness was 36.2 cases/100 cows/month, with correspondent rates of 27.4, 31.9, 48.4, and 45.8 cases/100 cows/month in HGR, HNGR, CON-GR, and CON-NGR, respectively. Time to first lameness event was significantly higher in HGR (mean ± S.E; 8.12 ± 0.15) compared to CON-GR (7.36 ± 0.26), and in HNGR (8.05 ± 0.16) compared to CON-NGR (7.39 ± 0.23). The prevalence of hoof lesions in the enrolled cows was 36.9%, with a higher prevalence in CON-GR (48.8%) than HGR (23.2%), and in CON-NGR (52.6%) compared to HNGR (32.2%). The majority of hoof lesions were non-infectious in grazing (HGR vs. CON-GR; 21.3% vs. 33.3%) and non-grazing herds (HNGR vs. CON-NGR; 25.0% vs. 40.4%). The risk of lameness was higher in underconditioned cows (Hazard ratio; HR = 3.1, 95% CI 1.2-7.4), presence of hoof lesion (HR = 33.1, 95% CI 17.6-62.5), and there was variation between farms. Aside HT, lower parity (OR = 0.4, 95% CI 0.2-0.8), normal hock condition (OR = 0.06; 95% 0.01-0.29), and absence of overgrown hoof (OR = 0.4; 95% 0.2-0.7) were protective against non-infectious hoof lesions. Functional HT is beneficial as a lameness preventive strategy during lactation; however, ensuring older cows are in good body condition and free from hock injuries are equally important.